The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/su15020940
|View full text |Cite
|
Sign up to set email alerts
|

Gamified Project-Based Learning: A Systematic Review of the Research Landscape

Abstract: The information era puts higher requirements on current students’ learning methods to develop 21st-century skills. Project-based learning (PBL) and gamified learning have been two effective learning approaches, leading to an innovative exploration of combining both to improve learning outcomes. This study presents a systematic review of the literature published on “gamified PBL” (GPBL) over the past six years, focusing on GPBL approaches, learning outcomes, technical tools and theories. The results show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 65 publications
0
1
0
1
Order By: Relevance
“…Chikurteva, A et al explore the role of communication technologies in PBL and the benefits and problems of implementing PBL and propose a conceptual model of a PBL platform in education [7]. Huang, WD et al review the literature on "gamified PBL" (GPBL), which combines project-based learning and gamified learning, focusing on GPBL methodology, learning outcomes, technological tools, and theories [8]. Saad A et al review the literature related to project-based learning (PBL) and computational thinking (CT) and find a lack of methodological guidance for implementing PBL-CT, identifying several common factors for the PBL-CT framework or models [9].…”
Section: What Is the Current Status Of Domestic And International Res...mentioning
confidence: 99%
“…Chikurteva, A et al explore the role of communication technologies in PBL and the benefits and problems of implementing PBL and propose a conceptual model of a PBL platform in education [7]. Huang, WD et al review the literature on "gamified PBL" (GPBL), which combines project-based learning and gamified learning, focusing on GPBL methodology, learning outcomes, technological tools, and theories [8]. Saad A et al review the literature related to project-based learning (PBL) and computational thinking (CT) and find a lack of methodological guidance for implementing PBL-CT, identifying several common factors for the PBL-CT framework or models [9].…”
Section: What Is the Current Status Of Domestic And International Res...mentioning
confidence: 99%
“…Using a qualitative approach to investigate the students' learning experience by creating a Computer Support Collaborative Learning Environment (Perales, 2022), it was found that such an environment can enhance the students' learning experience. Collaborative initiatives, support for each other, and group projects can enhance the social learning experience among students (Zhang, et al, 2023). A supportive learning environment offers an opportunity to learn from each other's learning experiences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A lo anterior se suma que las aulas del siglo XXI se están transformando lentamente en pequeños grupos colaborativos que están pasando de un aprendizaje pasivo a entornos de aprendizaje basados en proyectos (Kokotsaki et al, 2016;Helle et al, 2006), utilizando la robótica como un intento de motivar, involucrar y aumentar la retención y el interés de los estudiantes (Cappelleri y Vitoroulis, 2013). El ABP se ha implementado en el aprendizaje de la robótica a nivel superior desde hace varios años (Valls, 2022;Walter y Spath, 2015;Cabre et al, 2013;Quidway, 2011;Price et al, 2010;Varner, 1998) y hace referencia a un modelo de aprendizaje que se organiza en torno a proyectos (Huang et al, 2022), que fomenta la práctica y la relación del conocimiento con la vida diaria (Brin y Shypilova, 2022), contribuyendo a un aprendizaje significativo y profundo (Kızkapan y Bektaş, 2017).…”
unclassified